A comparative analysis of six bionic design methods. (1st January 2011) - Coelho, Denis A.; Versos, Carlos A.M.
Design inspired by nature is getting to the forefront of the search for environmental sustainability. A number of design methods, intended especially to guide students and professionals from several disciplines in carrying out the development of biologically inspired design, have been proposed. The paper establishes a comparative analysis between six methods. These are presented in similar depth, with the parameters of analysis described. The analysis is based on scrutiny of the methods, in relation to the support given towards the attainment of four goals (form optimisation, organisational effectiveness, multiple requirements satisfaction and paradigm innovation for improved functional performance), considered of paramount importance to typical design endeavours aiming at achieving innovative concepts, optimisation of specific features or performance and environmental sustainability. The comparative analysis is intended to support designers in selecting a method that is adequate to the problem at hand. The analysis also identifies goals where the methods considered offer no or reduced support for their attainment, identifying the need for novel methodological proposals. As a conclusion, the requirement to integrate validation activities in the bionic design processes is emphasised.